2019
DOI: 10.1186/s12906-019-2633-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of six Chinese herb formulas for acute exacerbation of chronic obstructive pulmonary disease: a systematic review and network meta-analysis

Abstract: Background: Six Chinese herb formulas, namely, the Weijing decoction (WJ), the Maxingshigan decoction (MXSG), the Yuebijiabanxia decoction (YBBX), the Qingqihuatan decoction (QQHT), the Dingchuan decoction (DC) and the Sangbaipi decoction (SBP), are commonly used, along with routine pharmacotherapy, to manage the acute exacerbation of chronic obstructive pulmonary disease (AECOPD). In this study, we conducted a systematic review to summarize the efficacy of these six formulas, and we also conducted a network m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…MSD has been widely used in the prevention and treatment of respiratory diseases. Several studies had verified its antiviral effects mediated by regulating immune function, suppressing inflammatory cytokine storm, and improving oxygenation and forced expiratory volume/second (FEV1) [ 13 , 14 ]. SMD has been shown to alleviate pathological lung damage and inflammation in rats with asthmatic pneumonia by enhancing immune activity and downregulating the expression of thymic stromal lymphopoietin (TSLP), toll-like receptor 4 (TLR4), and nuclear factor- κ B (NF- κ B) in lung tissue [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSD has been widely used in the prevention and treatment of respiratory diseases. Several studies had verified its antiviral effects mediated by regulating immune function, suppressing inflammatory cytokine storm, and improving oxygenation and forced expiratory volume/second (FEV1) [ 13 , 14 ]. SMD has been shown to alleviate pathological lung damage and inflammation in rats with asthmatic pneumonia by enhancing immune activity and downregulating the expression of thymic stromal lymphopoietin (TSLP), toll-like receptor 4 (TLR4), and nuclear factor- κ B (NF- κ B) in lung tissue [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies report adverse events of any cause and data are summarized in Table 5. Of these, four studies have no adverse events throughout the study period [28,[66][67][68]. Wang reports 2 cases of nausea, Liu reports 1 case of mouth dryness, and Huang reports 3 cases of acute exacerbation with hospitalization.…”
Section: Primary Outcome: Adverse Events Of Any Causementioning
confidence: 99%
“…Of these, nine studies used St. George's Respiratory Questionnaire (SGRQ) [69][70][71][72][73][74][75][76][77]. Eight studies used COPD-Quality of Life (COPD-QoL) questionnaire [54,67,[78][79][80][81][82][83].…”
Section: Primary Outcome: Adverse Events Of Any Causementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, clinical studies have also shown that Sangbaipi Decoction combined with conventional Western medicine treatment of AECOPD can improve the clinical efficacy, [ 5 ] but there are some limitations, such as single reports, scattered research, small sample size. With the development of evidence-based medicine, it has opened up new research fields in the clinical efficacy evaluation of Chinese medicine, produced new research ideas and methods, and promoted the progress of clinical research in Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%